Synthesis and evaluation of analogues of the tuberculosis drug bedaquiline containing heterocyclic B-ring units. Issue 23 (1st December 2017) - Choi, Peter J.; Sutherland, Hamish S.; Tong, Amy S.T.; Blaser, Adrian; Franzblau, Scott G.; Cooper, Christopher B.; Lotlikar, Manisha U.; Upton, Anna M.; Guillemont, Jerome; Motte, Magali; Queguiner, Laurence; Andries, Koen; et al.
Graphical abstract: Abstract: Analogues of bedaquiline where the phenyl B-unit was replaced with monocyclic heterocycles of widely differing lipophilicity (thiophenes, furans, pyridines) were synthesised and evaluated. While there was an expected broad positive correlation between lipophilicity and anti-TB activity, the 4-pyridyl derivatives appeared to have an additional contribution to antibacterial potency. The majority of the compounds were (desirably) more polar and had higher rates of clearance than bedaquiline, and showed acceptable oral bioavailability, but there was only limited (and unpredictable) improvement in their hERG liability.